A De novo Transcriptomic Approach to Identify Flavonoids and Anthocyanins “Switch-Off” in Olive (Olea europaea L.) Drupes at Different Stages of Maturation - Iaria, Domenico L.; Chiappetta, Adriana; Muzzalupo, Innocenzo (Frontiers in Plant Science, 2016)
During ripening, the fruits of the olive tree (Olea europaea L.) undergo a progressive chromatic change characterized by the formation of a red-brown "spot" which gradually extends on the epidermis and in the innermost part of the mesocarp. This event finds an exception in the Leucocarpa cultivar, in which we observe a destabilized equilibrium between the metabolisms of chlorophyll and other pigments, particularly the anthocyanins whose switch-off during maturation promotes the white coloration of fruits. Despite its importance, genomic information on the olive tree is still lacking. Different RNA-seq libraries were generated from drupes of ‘Leucocarpa’ and ‘Cassanese’ olive genotypes, sampled at 100 and 130 days after flowering (DAF), and were used in order to identify transcripts involved in the main phenotypic changes of fruits during maturation and their corresponding expression patterns. A total of 103,359 transcripts were obtained and 3792 and 3064 were differentially expressed in ‘Leucocarpa’ and ‘Cassanese’ genotypes, respectively, during 100-130 DAF transition. Among them flavonoid and anthocyanin related transcripts such as phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), chalcone synthase (CHS), chalcone isomerase (CHI), flavanone 3-hydroxylase (F3H), flavonol 3’-hydrogenase (F3'H), flavonol 3’5’-hydrogenase (F3'5'H), flavonol synthase (FLS), dihydroflavonol 4-reductase (DFR), anthocyanidin synthase (ANS), UDP-glucose:anthocianidin:flavonoid glucosyltransferase (UFGT) were identified. These results contribute to reducing the current gap in information regarding metabolic processes, including those linked to fruit pigmentation in the olive.